One More Word: The Translator’s Archive in Secession with Insecession - Angela Carr (Sillages Critiques)
This paper explores the poetics and politics of translation. It argues for an avant-garde approach to poetry translation that places translation alongside poetry as a creative practice. In Erin Moure and Chus Pato’s Secession with Insecession, an encounter between two poets produces a “third text” that disrupts the linear narrative of translation (from source to target text). Beside Pato’s Secession, Moure’s Insecession, is not only a creative work — inscribed both between and beyond the translation and the original — but also an archive of the encounter of translation. In terms of publishing and circulation, Secession with Insecession also raises critical questions about whose writings may be supported by a national literary community and the nation at large. This paper argues that Moure’s third text supplies a line of flight from exclusionary rulings on belonging. Secession with Insecession, an avant-garde poetic work, challenges established reading practices, suggesting its own mise en abyme as the ruins of poetry.